Higher Wear-Rate of Third-Generation Metal-Backed Reflection Cups with Eto-Sterilised UHMWPE at a Mean 13 Years Follow-up. Issue 6 (November 2014) - Hengst, David M.; Thomsen, Per B.; Homilius, Morten; Hansen, Torben B.; Stilling, Maiken
Polyethylene (PE) wear and osteolysis is a recognised problem with non-cross linked PE liners and first generation modular cup designs. Wear particles induce osteolysis leading to aseptic loosening. We retrospectively compared the linear PE wear and implant survival and revision rates of the Reflection Cup and the Duraloc 300. After a mean clinical follow-up of 13 years (range 11-15 years), the 2D linear PE wear-rate of the Reflection liner (n = 68) was 0.23 mm/year, with a mean total wear of 3.14 mm (1.04-7.36), SD 1.45. The wear-rate of the Duraloc 300 cups (n = 32) was 0.14 mm/year, with a mean total wear of 1.84 mm (0.55-4.63), SD 1.07. The difference in PE wear-rate as well as mean total wear was highly significant (p = 0.0001). There was a positive correlation between wear-rate and both Oxford Hip Score and Harris Hip Score (p = 0.02). Large acetabular cup size (>54 mm), HA coating on the stem and age <50 years did not influence PE wear. The higher wear-rate in the Reflection liners could be related to the EtO sterilisation. Intermediate and long-term follow-up is advisable.